Assessing Hafting Adhesive Efficiency in the Experimental Shooting of Projectile Points: A new Device for Instrumented and Ballistic Experiments. (6th May 2015) - Gaillard, Y.; Chesnaux, L.; Girard, M.; Burr, A.; Darque‐Ceretti, E.; Felder, E.; Mazuy, A.; Regert, M.
Abstract : With the aim of providing better control of shooting experiments performed with replicas of prehistoric projectiles, we have conducted an instrumental archaeology study on the efficiency of prehistoric projectile points by placing emphasis on their adhesion and ballistic characteristics. In order to avoid any reproducibility problems, hafting adhesives were made with controlled mixtures of commercial rosin (also called 'colophany') and beeswax added as a plasticizer. An original experimental device has been developed to instrument a bow, allowing the control of both the trajectories and the velocities of the different shoots. In the course of an experimental programme on Sauveterrian microliths from the Mesolithic period of the South of France, the experimental system was applied to composite replica projectile tips of Mesolithic hunters. Arrows being shot at transparent targets were filmed in order to evaluate the penetration length and residual damage. Interestingly, this study reveals that the properties of the mixture are highly dependent on the velocity of the arrows. It was shown that—contrary to previous experiments that usually used a mixture in which rosin predominates— the most efficient adhesive is made of 70 wt% beeswax with only 30 wt% rosin. This result is of great importance for improving further shooting experiments and overcoming the problems frequently mentioned due to the loss of the flint armatures before they reach the animal target, or at least before penetration. When using this appropriate mixture, the lateral armatures are resistant to most of the shots. Experiments performed on real boars' flesh have also shown that the presence of lateral microliths allows the laceration inflicted on the target to be enlarged. Finally, a critical parameter has been identified, which is the location on the arrow of the microlithic element.